Laser-based single-axon transection for high-content axon injury and regeneration studies. - Darío Kunik (Public Library of Science (PLoS), 2011)
The investigation of the regenerative response of the neurons to axonal injury is essential to the development of new axoprotective therapies. Here we study the retinal neuronal RGC-5 cell line after laser transection, demonstrating that the ability of these cells to initiate a regenerative response correlates with axon length and cell motility after injury. We show that low energy picosecond laser pulses can achieve transection of unlabeled single axons in vitro and precisely induce damage with micron precision. We established the conditions to achieve axon transection, and characterized RGC-5 axon regeneration and cell body response using time-lapse microscopy. We developed an algorithm to analyze cell trajectories and established correlations between cell motility after injury, axon length, and the initiation of the regeneration response. The characterization of the motile response of axotomized RGC-5 cells showed that cells that were capable of repair or regrowth of damaged axons migrated more slowly than cells that could not. Moreover, we established that RGC-5 cells with long axons could not recover their injured axons, and such cells were much more motile. The platform we describe allows highly controlled axonal damage with subcellular resolution and the performance of high-content screening in cell cultures.